Missing power: Nostalgia and disillusionment among Southern California water engineers. (September 2021) - Randle, Sayd
California's sprawling network of aqueducts and dams is often cited as the embodiment of a high-modernist approach to resource management. But while once widely celebrated, in recent decades this infrastructural system and the institutions that manage it have been the subject of growing criticism and shrinking funding streams. Based on ethnographic research among employees at several California water agencies, this article explores the sense of nostalgia and diminished power experienced by the workers tasked with overseeing these networks. These emic perspectives are frequently articulated in the form of unfavorable comparisons to an imagined past, when the workers believe that their agencies were better resourced and civil engineers' technical expertise was more respected by the public that they served. Analyzing these stories of declining influence and capacity, the article shows how understandings of individual and institutional power can be conditioned by past paradigms of regional development and technocratic statecraft.